Circulating tumor DNA identified by targeted sequencing in advanced-stage non-small cell lung cancer patients. Issue 2 (28th January 2016) - Xu, Song; Lou, Feng; Wu, Yi; Sun, Da-Qiang; Zhang, Jing-Bo; Chen, Wei; Ye, Hua; Liu, Jing-Hao; Wei, Sen; Zhao, Ming-Yu; Wu, Wen-Jun; Su, Xue-Xia; et al.
Highlights: The Ion PGM and AmpliSeq cancer panel can detect plasma ctDNA mutations from NSCLC. ctDNA mutations in plasma are highly concordant to primary tumor tissue of NSCLC. Our panel could be implemented for clinical use in a variety of advanced cancers. Abstract: Non-small cell lung cancers (NSCLC) have unique mutation patterns, and some of these mutations may be used to predict prognosis or guide patient treatment. Mutation profiling before and during treatment often requires repeated tumor biopsies, which is not always possible. Recently, cell-free, circulating tumor DNA (ctDNA) isolated from blood plasma has been shown to contain genetic mutations representative of those found in the primary tumor tissue DNA (tDNA), and these samples can readily be obtained using non-invasive techniques. However, there are still no standardized methods to identify mutations in ctDNA. In the current study, we used a targeted sequencing approach with a semi-conductor based next-generation sequencing (NGS) platform to identify gene mutations in matched tDNA and ctDNA samples from 42 advanced-stage NSCLC patients from China. We identified driver mutations in matched tDNA and ctDNA in EGFR, KRAS, PIK3CA, and TP53, with an overall concordance of 76%. In conclusion, targeted sequencing of plasma ctDNA may be a feasible option for clinical monitoring of NSCLC in the near future.